Not in vain ; 16th what God hath wrought amongst the Kanakas in Queensland being Report of the Queensland Kanaka Mission for the year 1901-1902 (1902)
Contents includes : Queensland Kanaka Mission : Object and principles (revised).
Photocopy.
Keywords: Queensland Kanaka Mission; Brethren movement -- missions -- Australia -- history